Evaluation of bacterial metabolic products in saliva after ozone treatment on the basis of nuclear magnetic resonance spectroscopy (NMR) – own investigations - Pijankowska-Beksa, Lidia; Fabiańska, Anna; Pacholczyk-Sienicka, Barbara; Jankowski, Stefan; Szczepańska, Joanna (Journal of Stomatology, 2015)
Introduction. The presence of ‘Streptococcus mutans’ is considered to be the main cause of carious lesions. Ozone has, among others, antibacterial and remineralisation potential. Pyruvic acid, produced by cariogenic bacteria, is degraded by ozone to carbon dioxide and acetate or other organic acids of high pKa. Nuclear Magnetic Resonance (NMR) can determine the character and degree of oxidation of organic substances placed in the magnetic field. It is becoming more widely available as a diagnostic technique, and is used in the chemical analysis of various body fluids such as urine, serum, plasma, cerebrospinal fluid, bile, seminal fluid, saliva, sweat, tears and amniotic fluid. Aim of the study. To identify metabolites characteristic of saliva, to determine the connection between changes of its chemical composition and applied ozone therapy, and to assess the effectiveness of the said therapy in the treatment of dental caries. Material and methods. The saliva of patients undergoing ozone therapy (twenty-four children aged 6-8) was examined by NMR. Before the procedure, the state of the deciduous and permanent teeth was assessed, as well as oral hygiene. After ozone treatment and topical fluoridation, the resting mixed saliva was collected from patients at four time points. The saliva samples were then evaluated for the presence of glucose, pyruvate, acetate, and formate using NMR. The results were statistically analyzed. Results. The conducted studies showed a decrease in the signal intensity of glucose and pyruvate in saliva after the application of ozone. The average concentration of glucose was 0.311 mM before the treatment, 0.172 mM after the ozone treatment, 0.113 after 15 minutes and 0.105 mM after 30 minutes. The average concentration of pyruvate was 0.113 mM before surgery, 0.082 mM immediately afterwards, 0.066 mM after 15 minutes, and 0.054 mM after 30. In the case of acetate and formate, the results were not identical with measurements under in vitro conditions. Conclusions. NMR spectroscopy provides an insight into the nature and extent of oxidation of chemical compounds contained in saliva after the application of ozone in the prophylactic treatment within the oral cavity.